Approximating the nonlinear density dependence of electron transport coefficients and scattering rates across the gas–liquid interface. (14th February 2018) - Garland, N A; Boyle, G J; Cocks, D G; White, R D
Abstract: This study reviews the neutral density dependence of electron transport in gases and liquids and develops a method to determine the nonlinear medium density dependence of electron transport coefficients and scattering rates required for modeling transport in the vicinity of gas–liquid interfaces. The method has its foundations in Blanc's law for gas-mixtures and adapts the theory of Garland et al (2017 Plasma Sources Sci. Technol. 26 ) to extract electron transport data across the gas–liquid transition region using known data from the gas and liquid phases only. The method is systematically benchmarked against multi-term Boltzmann equation solutions for Percus–Yevick model liquids. Application to atomic liquids highlights the utility and accuracy of the derived method.